2019
DOI: 10.1073/pnas.1905561116
|View full text |Cite
|
Sign up to set email alerts
|

RAMP3 determines rapid recycling of atypical chemokine receptor-3 for guided angiogenesis

Abstract: Receptor-activity–modifying proteins (RAMPs) are single transmembrane-spanning proteins which serve as molecular chaperones and allosteric modulators of G-protein–coupled receptors (GPCRs) and their signaling pathways. Although RAMPs have been previously studied in the context of their effects on Family B GPCRs, the coevolution of RAMPs with many GPCR families suggests an expanded repertoire of potential interactions. Using bioluminescence resonance energy transfer-based and cell-surface expression approaches,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 36 publications
3
79
0
Order By: Relevance
“…Furthermore, it is worth mentioning that, although best studied and characterized, the modulating action of RAMPs is not exclusive to CTR and CLR. In this sense, RAMPs also operate as molecular chaperones and allosteric modulators of several GPCRs and their signaling pathways, including glucagon, growth hormone releasing hormone (GHRH), parathyroid hormone and chemokine receptors among others (82,88,89).…”
Section: Particularities Of the Am (And Calcitonin-like Peptide) Recementioning
confidence: 99%
“…Furthermore, it is worth mentioning that, although best studied and characterized, the modulating action of RAMPs is not exclusive to CTR and CLR. In this sense, RAMPs also operate as molecular chaperones and allosteric modulators of several GPCRs and their signaling pathways, including glucagon, growth hormone releasing hormone (GHRH), parathyroid hormone and chemokine receptors among others (82,88,89).…”
Section: Particularities Of the Am (And Calcitonin-like Peptide) Recementioning
confidence: 99%
“…To explore the potential mechanisms involved in Bevacizumab resistance in CRC, we used TCGA database to perform ETV5-related GSEA analysis. We found that ETV5 expression was significantly associated with the activation of a chemokine signaling pathway, and this could also contribute to angiogenesis in a number of cancers 29,30 . Of the significantly enriched genes, four genes were proangiogenic factors, including CXCL11, CXCL5, CCL2, and CCL13 19 .…”
Section: Discussionmentioning
confidence: 86%
“…It should be noted that ETV5 was positively related to the activation of a chemokine signaling pathway (Fig. 3a ) that was involved in angiogenesis in cancers 29 , 30 . In this pathway, 26 genes were significantly enriched and are further displayed according to a heatmap (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to explore the potential mechanisms involved in bevacizumab resistance in CRC, we used the TCGA data to performed ETV5-related GSEA analysis. We found that ETV5 expression was signi cantly associated with activation of chemokine signaling pathway, which could also contribute to angiogenesis in many cancers [29,30]. In the signi cantly enriched genes, four genes were also proangiogenic factors, such as CXCL11, CXCL5, CCL2, CCL13 [19].…”
Section: Discussionmentioning
confidence: 88%
“…It was worth noting that ETV5 positively related to activation of chemokine signaling pathway (Fig. 3a), which was involved in angiogenesis in cancers [29,30]. In this pathway, 26 genes were signi cantly enriched and further displayed by heatmap (Fig.…”
Section: Statisticsmentioning
confidence: 99%